Qualidade de vida no trabalho e Síndrome de Burnout em profissionais públicos e privados de Santa Cruz do Sul/RS - Brito, Lucas Charão (2014)
Considering that work represents the main goal in people lives, the Quality of Work Life (QWL) and occupational health become relevant when work market is instable and insecure (COHEN, 2003). Regarding this, the biopsychosocial approach of QWL assessment understand the individual as part of the whole, comprehending its own potentials and biological, psychological and organizational aspects, which contribute to frame the human condition (LIMONGI-FRANÇA, 2007). Besides QWL, the Burnout Syndrome (MASLACH e LEITER, 1999; BENEVIDES-PEREIRA, 2010; ENACHE, 2013) has been treated as one of the harm aspects of the physical and mental health worker, also being related to the operational and organizational performance, which may be an important factor on the interpersonal relationships as well as on social contexts. The study has as main goal identifying the possible relations between the Quality of Work Life and the Burnout Syndrome. Regarding that, it was performed a survey applied to a sample of 575 public and private workers from Santa Cruz do Sul/RS. The research was developed based on a descriptive and exploratory approach, considering two theoretical models: (1) Maslach Burnout Inventory (MBI-GS) developed by Maslach (1996); 2) Biopsychosocial Model (BPSPO-96) developed by Limongi-França (1996). The data shown the general characterization of the sample profile is mainly comprehended by women, married, graduated, and age from 26 to 35 years. Regarding to the professional profile it was noticed that the majority works in the private sector developing operational activities. Beyond understanding the levels of QWL and Burnout, this study sought signs that would enable the targeting of strategies that would minimize dissatisfaction and illness in the workplace. The main goal of the study was answered by applying the correspondence analysis technique. Can be highlighted that the results have evidenced a direct relationship between the aspects of Biopsychosocial Model of QWL and the dimensions of Burnout. However, it can be noticed that the biological and psychological aspects do not have any relation with the correspondence analysis with the Burnout. On the other hand, social and organizational aspects, in low levels, present relation with the Burnout in high level. In this sense, the results from this analysis have shown that generally the satisfaction with QWL aspects in low levels results in emotional exhaustion depersonalization in high levels as well as the Burnout Syndrome. It is evidenced that the contribution of this study is located at the identification of the relationships between the Burnout and the QWL aspects. It can be highlighted the need of a deeper analysis on the results, investigating different variables and different populations as well as specific occupations related to work experience, once the literature related to the triangulation of themes is still incipient in Brazil. As suggestions of future works, is pointed the reproduction of the study in different contexts as well as the application of the structural equation modeling, aiming to propose a model that explains the Burnout Syndrome in Brazilian works.